Pengaruh Laba, Beban Bunga, Biaya Operasional, dan Aset Lancar Terhadap Pph Badan Pada BUMN Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Evana, Melisa Rosa; Lubis, Nurul Izzah; Masyitah, Emi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Corporate Income Tax Payable is the tax levied on a business entity’s taxable income under applicable tax regulations. This study examines the partial and simultaneous effects of Profit, Interest Expense, Operating Expenses, and Current Assets on Corporate Income Tax Payable for state-owned enterprises listed on the Indonesia Stock Exchange from 2019 to 2023. A quantitative approach was used with SPSS version 25. Samples were selected using purposive sampling according to predetermined criteria, yielding ten companies. Data were analyzed using multiple linear regression, classical assumption tests, t-tests, an F-test, and the coefficient of determination. Results from the partial hypothesis tests indicate that Profit has a positive and significant effect on Corporate Income Tax Payable; Interest Expense has a negative and significant effect; Operating Expenses have a positive and significant effect; while Current Assets show no significant effect. The F-test demonstrates that the four variables jointly influence Corporate Income Tax Payable. The model’s R² is 0.967, meaning 96.7% of the variation in Corporate Income Tax Payable is explained by the independent variables. The Adjusted R² of 0.964, which adjusts for the number of predictors, is similar, indicating model robustness. In conclusion, Profit, Interest Expense, and Operating Expenses are important determinants of Corporate Income Tax Payable among the sampled SOEs, while Current Assets are not. Recommendations include enhancing financial transparency, reviewing interest policies, and optimizing operational cost management to improve tax efficiency and strengthen fiscal compliance among SOEs moving forward and governance